Normothermic regional perfusion for donation after circulatory death in lung transplantation - Gorton, Andrew J.; Mohammadi, Daniel K.; Malik, Mohammad J.; Keshavamurthy, Suresh (Frontiers in Cardiovascular Medicine, 2025)
Donor supply of lung allografts lags behind the waitlist demand leading to an ongoing attempt to expand the donor pool. Recently this has mean increased utilization of donation after circulatory death (DCD). The concern about graft quality with this approach is more acute in fields with organs especially sensitive to ischemia, such as the lungs. One strategy being utilized to limit ischemic time is in situ thoracoabdominal normothermic regional perfusion with the use of extracorporeal membrane oxygenation (ECMO) or cardiopulmonary bypass (CPB) instituted after declaration of circulatory death to restore organ perfusion. This method is thought to decrease ischemic time, allow for correction of metabolic abnormalities, and provide longer for organ procurement. The data evaluating both the graft function and clinical outcomes following donation after circulatory death with normothermic regional perfusion (DCD-NRP) are growing with early results suggesting equivalent graft recovery and similar survival. This review aims to gather details of the procedure utilization, graft function, and patient outcomes and summarize the outcomes from a growing pool of data.